IMPLEMENTATION OF CONTINUOUS SERVICE IMPROVEMENT CONCEPT IN HEALTHCARE ORGANIZATIONS: Continuous Service Improvement Concept - Haq, Muhammad Ahsan ul; Ashraf, Muhammad Salman (Pakistan Armed Forces Medical Journal, 2015)
INTRODUCTIONHealth is a state of complete physical, mental and social well being and not merely an absence of disease or infirmity that leads to the ability to lead a socially and economically productive life1. Health care includes meeting both medical and non-medical needs of the patient. It is integral to Total Quality Management (TQM) and Quality Assurance (QA) approach in quality for efficiency benefits². CSI is not a new concept and originally developed by manufacturing and service industries, with substantial benefit to organizations. Its success at improving productivity over many years has led to it being adopted by health care systems in international healthcare (UK and USA)3. Continuous Service Improvement (CSI) is adopted for initiatives both at national level and organizational level as strategic change tool. This concept is effectively applicable in all service sector and government sponsored health care organizations, where healthcare delivery is government responsibility. Likewise, health care in defence services medical setups has a peculiar environment, where services are free and providers are accountable. Constraints of cost and resource imbalance and ever increasing patient turnover are the key limiting factors. Resultantly, hospital improvement activities are more organization/ sponsor driven, rather than patient centered. This gap necessitates introduction of CSI process in defence services and similar health care delivery system.